A Systematic Approach to Identify Sources of Abnormal Interior Noise for a High-Speed Train - Jie Zhang; Xinbiao Xiao; Xiaozhen Sheng; Zhihui Li; Xuesong Jin (Shock and Vibration)
A systematic approach to identify sources of abnormal interior noise occurring in a high-speed train is presented and applied in this paper to resolve a particular noise issue. This approach is developed based on a number of previous dealings with similar noise problems. The particular noise issue occurs in a Chinese high-speed train. It is measured that there is a difference of 7 dB(A) in overall Sound Pressure Level (SPL) between two nominally identical VIP cabins at 250 km/h. The systematic approach is applied to identify the root cause of the 7 dB(A) difference. Well planned measurements are performed in both the VIP cabins. Sound pressure contributions, either in terms of frequency band or in terms of facing area, are analyzed. Order analysis is also carried out. Based on these analyses, it is found that the problematic frequency is the sleeper passing frequency of the train, and an area on the roof contributes the most. In order to determine what causes that area to be the main contributor without disassembling the structure of the roof, measured noise and vibration data for different train speeds are further analyzed. It is then reasoned that roof is the main contributor caused by sound pressure behind the panel. Up to this point, panels of the roof are removed, revealing that a hole of 300 cm2 for running cables is presented behind the red area without proper sound insulation. This study can provide a basis for abnormal interior noise analysis and control of high-speed trains.